The Correlation of Regulatory T (TReg) and Vitamin D3 in Pediatric Nephrotic Syndrome - Yunika Nurtyas; Krisni Subandiyah; Loeki Enggar Fitri (Journal of Tropical Life Science, 2018)
Nephrotic syndrome (NS) is an autoimmune disease that correlates to the imbalance of regulatory T cells (TReg). This study was aimed to investigate the effect of vitamin D as adjuvant therapy of TReg population in pediatric nephrotic syndrome. This study was designed randomized clinical trial, double blind, with pre- and post-test control groups involving 15 subjects newly diagnosed with NS. Subjects were divided into 2 groups, namely K1 for group treated with prednisone+vitamin D and K2 group for prednisone treatment only. The population of TReg in peripheral blood mononuclear cells (PBMC) was analyzed using flowcytometry. Vitamin D serum level was measured through ELISA method. Results showed that there was a significant elevation of TReg (independent t-test, p = 0.010) in K1 group, which was higher than in K2 group. The Pearson test in the K1 group showed that vitamin D level was positively correlated with TReg (p = 0.039, r = 0.779).